Biological methods for odor treatment – A review. (20th May 2017) - Barbusinski, Krzysztof; Kalemba, Katarzyna; Kasperczyk, Damian; Urbaniec, Krzysztof; Kozik, Violetta
Abstract: Odors are emitted from agricultural and industrial activities, such as animal farms, rendering plants, wastewater treatment plants, waste treatment or disposal facilities, paint shops, oil refineries, pulp and paper mills, and various chemical industries. Effects of this kind of air pollution may include: impairment of the quality of the environment; interference with business activities; discomfort, harm or impairment of the safety of any person; rendering any property, plant or animal unsuitable for human use. Odor treatment technologies can be classified into three categories, namely ones employing chemical (thermal oxidation, catalytic oxidation, ozonation), physical (condensation, adsorption, absorption) and biological (using biofilters, biotrickling filters, bioscrubbers and other bioreactor types) treatment methods. An important advantage of biological treatment methods over physical and chemical technologies is that the biological processes can be conducted at moderate temperatures (10–40 °C) and atmospheric pressure. Moreover, microbial degradation processes are generally oxidative in nature and produce compounds such as carbon dioxide, water, sulfate and nitrate that are ecologically safe. Applications of biological odor treatment date back to 1950ties. Initially, simple biofilters with soil beds have been employed and later, the use of other bed materials in more advanced filter structures has been reported and more sophisticated types of filtration equipment such as biotrickling filters and bioscrubbers have been developed. On the basis of accumulated experience, some more process options and equipment types for the application of biological methods emerged in recent years. During more than 30 years covered by the present review, biological methods of odor treatment have matured to become a well-developed field of process technology. In order to provide an overview of the state of the art, process principles and characteristics including the use of various microorganisms and nutrients, variations in equipment design and application ranges of the different odor treatment technologies are outlined and compared. Highlights: Odor abatement comprises legal, management, technology and monitoring issues. Odor treatment technologies based on biotechnology applications are reviewed. Biofiltration, biotrickling filtration and bioscrubbing are the main technologies. Three less known technologies based on specific bioreactor designs are also outlined. Further research is needed for continuing the refinement of odor treatment methods.